Contemplation on Development of Traditional Chinese Medicine Rehabilitation Science - Xiaodong FENG (康复学报)
Although the concept of Traditional Chinese Medicine Rehabilitation Science began in the 1980s, a lot of rehabilitation treatments were recorded on ancient classics of traditional Chinese medicine (TCM). For example, Huangdi Neijing emphasizes regulating mental states and body to enhance the ability of resistance to disease, the Five-Animal Exercises created by Huatuo can prevent disease and build body, acupuncture, moxibustion and medicine ironing also appear in the clinical and health literature of TCM. The theory and treatment methods of Traditional Chinese Medicine Rehabilitation Science originates in clinic and health preservation of TCM, but they have significant difference.The"healthy China 2030"planning outline demands that TCM plays the central role in rehabilitation therapy, this requires the use of TCM in the rehabilitation treatment should be with not only the increase of the quantity, but also the qualitative improvement. In the current rehabilitation therapy situation, Traditional Chinese Medicine Rehabilitation Science as an independent discipline should develop continuously and become one of the main force for the development of rehabilitation medical in China, only by exploiting advantages and advancing with the times.